PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Dewi Astuti; Erna Herlinawati; Dedi Supiyadi (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), and Earnings Per Share (EPS) on stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research method employed is a quantitative approach with an associative design using secondary data obtained from companies’ annual reports and analyzed through multiple linear regression. The results show that partially DER, ROA, and EPS do not have a significant effect on stock prices. However, simultaneously DER, ROA, and EPS have a significant effect on stock prices. In conclusion, although each financial ratio individually does not significantly influence stock prices, the combination of DER, ROA, and EPS collectively explains stock price movements in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Keywords: Debt To Equity Ratio, Return On Assets, Earnings Per Share, Stock Price, Food And Beverage Companies